The Effect of Circuit Training and Beetroot Training on the Increased Endurance of Karate Athletes - Sari, Liliana Puspa; Sundari, Della; Hendrawan, Dicky; Karo, Alan Alfiansyah Putra Karo; Usman, Khairul (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
The purpose of this study was to determine the effect of Circuit Training training and beetroot giving to the improvement of endurance abilities in karate athletes. This research method using experimental methods. Population and sample were 10 athletes of Karate Dojo at SMA PAB 4 Sampali who were obtained by total sampling technique, then divided into two groups using matching pairing techniques, namely the Circuit Training training group and giving beets and without giving beets (control group). The research instrument for data collection using tests and measurements, namely the Bleeb test endurance test. The first hypothesis 0.120> 0.05, Ha is rejected, meaning that the first hypothesis Ho is accepted, there is no significant effect of Circuit Training training and Beetroot Training on the increase in athlete's endurance. The second hypothesis 0.183> 0.05, Ha is rejected, meaning that the conclusion of the second hypothesis Ho is accepted there is no significant effect of Circuit Training without giving beet fruit (control group) on the increase in athlete's endurance. The third hypothesis shows that the Sig. 0.757> 0.05, then Ha is rejected, that is, there is no significant difference between the average value of the post-training circuit training and the giving of beets between the experimental group without giving beets (control group).